DETERMINANTS OF EMPLOYEE PERFORMANCE IN SHARIA FINANCE COMPANIES IN INDONESIA - Asep Rovi Nurjaman; Ida Busnetty; Soeharjoto; Faisal, Yusuf (CV. Radja Publika, 2023)
This study aims to determine the effect of work motivation (X1), work environment (X2) and religiosity (X3) on employee performance (Y2) of sharia finance companies in Indonesia with competence (Y1) as an intervening variable. Data collection was carried out through the distribution of questionnaires carried out to 380 employees of sharia finance companies in Indonesia. Data analysis in this study used SEM (Stuctural Equation Modelling) operated through the LISREL (Linear Structural Relationship) 8.70 program. The results showed that there was a positive and significant direct effect on the variables of work motivation (X1) and religiosity (X3) on employee performance (Y2) of Islamic finance companies with a coefficient of determination of 74%. In addition, the influence (indirect effect) of work motivation variables (X1), work environment (X2) and religiosity (X3) affect the performance of employees of Islamic finance companies with competence as an intervening variable